The decision maker's playbook : 12 mental tactics for thinking more clearly, navigating uncertainty and making smarter choices /: 12 mental tactics for thinking more clearly, navigating uncertainty and making smarter choices. (2019) - Mueller, Simon; Dhar, Julia
No abstract available